Enrichment and Genomic Characterization of a N2O-Reducing Chemolithoautotroph From a Deep-Sea Hydrothermal Vent - Mino, Sayaka; Yoneyama, Naoki; Nakagawa, Satoshi; Takai, Ken; Sawabe, Tomoo (Frontiers in Bioengineering and Biotechnology, 2018)
Nitrous oxide (N2O) is a greenhouse gas and also leads to stratospheric ozone depletion. In natural environments, only a single N2O sink process is the microbial reduction of N2O to N2, which is mediated by nitrous oxide reductase (NosZ) encoded by nosZ gene. The nosZ phylogeny has two distinct clades, clade I and formerly overlooked clade II. In deep-sea hydrothermal environments, several members of the class Campylobacteria are shown to harbor clade II nosZ gene and perform the complete denitrification of nitrate to N2; however, little is known about their ability to grow on exogenous N2O as the sole electron acceptor. Here, we obtained an enrichment culture from a deep-sea hydrothermal vent in the Southern Mariana Trough, which showed a respiratory N2O reduction with H2 as an electron donor. The single OTU belonging to the genus Hydrogenimonas within the class Campylobacteria was predominant throughout the cultivation period. Metagenomic analyses using a combination of short-read and long-read sequence data succeeded in reconstructing a complete genome of the dominant Hydrogenimonas OTU, which encoded clade II nosZ gene. This study represents the first cultivation analysis that shows the occurrence of N2O-respiring microorganisms in a deep-sea hydrothermal vent and provides the opportunity to assess their capability to reduce N2O emission from the environments.